2013
DOI: 10.1371/journal.pone.0066967
|View full text |Cite
|
Sign up to set email alerts
|

A New In Vivo Screening Paradigm to Accelerate Antimalarial Drug Discovery

Abstract: The emergence of resistance to available antimalarials requires the urgent development of new medicines. The recent disclosure of several thousand compounds active in vitro against the erythrocyte stage of Plasmodium falciparum has been a major breakthrough, though converting these hits into new medicines challenges current strategies. A new in vivo screening concept was evaluated as a strategy to increase the speed and efficiency of drug discovery projects in malaria. The new in vivo screening concept was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
(62 reference statements)
2
30
0
Order By: Relevance
“…Researchers have investigated the potential of the SCID huMouse model to translate estimated critical parameters to those observed in clinical trials (8). Recent studies demonstrated a poor correlation between parasite clearance rates (in vivo parasite reduction ratios) derived from mouse models and those reported from patients with malaria (8); this result is consistent with previous observations (27). However, the estimation of the IC 50 from the SCID huMouse model has yielded promising results as a surrogate of IC 50 in humans (8).…”
Section: Figuresupporting
confidence: 66%
“…Researchers have investigated the potential of the SCID huMouse model to translate estimated critical parameters to those observed in clinical trials (8). Recent studies demonstrated a poor correlation between parasite clearance rates (in vivo parasite reduction ratios) derived from mouse models and those reported from patients with malaria (8); this result is consistent with previous observations (27). However, the estimation of the IC 50 from the SCID huMouse model has yielded promising results as a surrogate of IC 50 in humans (8).…”
Section: Figuresupporting
confidence: 66%
“…The development of derivatives of 1 exhibiting greater in vivo antimalarial activity would therefore be desirable. In this vein, it is important to keep in mind the possible limitations [46] and slow clearance [47]) and artemisinin derivatives, exemplified by artesunate (recrudescence below 80 mg kg Ϫ1 day Ϫ1 via oral against P. vinckei) (48) are not optimal for treating rodent malaria parasites but are of unquestionable therapeutic value in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-based screening assays and early validation in animals provide multiple endpoints such as intracellular target specificity, cytotoxicity, bioavailability, pharmacokinetics and efficacy in a physiological context. Integrative information on safety and efficacy may facilitate the drug development process, and various cell-based proof-of-concept screening assays (Aubel et al, 2001;Gonzalez-Nicolini et al, 2004;Kim et al, 2015;Weber et al, 2008) and screening studies in animals (Higuera et al, 2013;Jimenez-Diaz et al, 2013;MacRae, 2013;Varble et al, 2013) have shown encouraging results.…”
Section: Discussionmentioning
confidence: 99%